HUBUNGAN ANTARA SOCIAL SUPPORT DAN LONELINESS DENGAN DISREGULASI EMOSI PADA REMAJA PELAKU SELF-HARM DI SEKOLAH MENENGAH KEJURUAN X KOTA BANDUNG - Saskia, Nabila Nurul; Sastri, Prinska Damara (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Adolescence is a developmental stage that is highly vulnerable to various emotional and social pressures. The inability to regulate emotions, also known as emotion dysregulation, can lead adolescents to engage in self-harming behaviors. This study aimed to examine the relationship between social support and loneliness with emotion dysregulation in adolescents who engage in self-harm. The study employed a quantitative, descriptive-correlational approach with purposive sampling techniques. The participants were 32 students from SMK X in Bandung who reported a history of self-harm within the past year. The instruments used in this study included the Multidimensional Scale of Perceived Social Support (MSPSS), the UCLA Loneliness Scale Version 3, and the Difficulties in Emotion Regulation Scale (DERS). The correlation analysis revealed a significant negative relationship between social support and emotion dysregulation (r = -0.286, p < 0.05), and a significant positive relationship between loneliness and emotion dysregulation (r = 0.387, p < 0.05). The multiple regression analysis showed that social support and loneliness simultaneously had a significant relationship with emotion dysregulation (F = 7.287, p = 0.003), with a coefficient of determination (R²) of 0.334. This indicates that 33.4% of the variance in emotion dysregulation is influenced by social support and loneliness. It can be concluded that lower levels of social support and higher levels of loneliness are associated with greater emotion dysregulation among adolescents. This study highlights the importance of enhancing social support and managing loneliness in efforts to prevent and address self-harm behavior in adolescents. ABSTRAKMasa remaja merupakan periode yang rentan terhadap berbagai tekanan emosional dan sosial. Ketidakmampuan dalam mengelola emosi atau disregulasi emosi dapat mendorong remaja untuk melakukan perilaku menyakiti diri sendiri (self-harm). Penelitian ini bertujuan untuk mengetahui hubungan antara social support dan loneliness dengan disregulasi emosi pada remaja pelaku self-harm. Penelitian menggunakan pendekatan kuantitatif deskriptif korelasional dengan teknik purposive sampling. Subjek penelitian berjumlah 32 siswa SMK X Kota Bandung yang memiliki riwayat self-harm dalam satu tahun terakhir. Alat ukur yang digunakan meliputi Multidimensional Scale of Perceived Social Support (MSPSS), UCLA Loneliness Scale Version 3, dan Difficulties in Emotion Regulation Scale (DERS). Hasil uji korelasi menunjukkan bahwa terdapat hubungan negatif signifikan antara social support dan disregulasi emosi (r = -0,286, p < 0,05), serta hubungan positif signifikan antara loneliness dan disregulasi emosi (r = 0,387, p < 0,05). Hasil uji regresi berganda menunjukkan bahwa social support dan loneliness secara simultan berhubungan signifikan dengan disregulasi emosi (F = 7,287, p = 0,003), dengan nilai koefisien determinasi (R²) sebesar 0,334. Artinya, 33,4% variabel disregulasi emosi dipengaruhi oleh social support dan loneliness. Dapat disimpulkan bahwa semakin rendah dukungan sosial dan semakin tinggi perasaan kesepian yang dialami remaja, maka semakin tinggi pula tingkat disregulasi emosi yang dirasakan. Penelitian ini menekankan pentingnya dukungan sosial dan pengelolaan kesepian dalam upaya pencegahan dan penanganan self-harm pada remaja.